Na-khi and Froto-Lolo-Burmese: a preliminary survey - Okrand, Marc (2024)
Na-khi is a Tibeto-Burman language spoken around the town of Likiang (or Li-chiang) in Yunnan, southern China. It has been classified (by Matisoff 1972) as a member of the Mosoid branch of the Loloid group of Lolo-Burmese languages within the Tibeto-Burman stock. The data upon which this preliminary survey is based are exclusively from Rock (1963) who makes a definite distinction between Na-khi and the related Moso.